Effects of scaling and root planing on gingival crevicular fluid vascular endothelial growth factor level in chronic periodontitis patients with and without diabetes mellitus: A clinicobiochemical study - Jayaraj Jishnu Pannicker; Dhoom Singh Mehta (Wolters Kluwer Medknow Publications, 2016)
Aim: To estimate the gingival crevicular fluid (GCF) level of vascular endothelial growth factor (VEGF) in periodontally healthy controls and chronic periodontitis (CP) patients with and without diabetes mellitus (DM) and also to investigate the effect of scaling and root planing (SRP) on the GCF VEGF level. Materials and Methods: One hundred and five patients were divided into three groups: Healthy (Group 1), CP (Group 2), and CP with DM (Group 3). Group 2 and Group 3 patients underwent SRP planning, and the cases were followed for 6 weeks. Periodontal clinical parameters such as plaque index, gingival index, probing pocket depth, and clinical attachment level were recorded at baseline and 6-week posttherapy. GCF samples collected from each patient were quantified for VEGF level using enzyme-linked immunosorbent assay. Results: The mean GCF VEGF level was increased in CP patients with and without DM compared to healthy patients and SRP therapy caused a statistically significant (P < 0.001) reduction in GCF VEGF level.Conclusion: VEGF is increased in GCF of CP patients with and without DM and that SRP substantially reduces its level in GCF.